2014
DOI: 10.1111/jpr.12076
|View full text |Cite
|
Sign up to set email alerts
|

Predicting lexical accent perception in native Japanese speakers: An investigation of acoustic pitch sensitivity and working memory

Abstract: Spoken language perception may be constrained by a listener's cognitive resources, including verbal working memory (WM) capacity and basic auditory perception mechanisms. For Japanese listeners, it is unknown how, or even if, these resources are involved in the processing of pitch accent at the word level. The present study examined the extent to which native Japanese speakers could make correctness judgments on and categorize spoken Japanese words by pitch accent pattern, and how verbal WM capacity and acoust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…At the opposite end of the perceptual spectrum are correctness judgment tasks, which require listeners to access a word's representation from memory, and can thus be used to examine lexical knowledge more directly than discrimination or categorization tasks. Goss and Tamaoka (2015) reported that L1 Japanese speakers from Tokyo-type accent regions were able to judge the correctness of highfrequency words at a mean accuracy of 93%, well above averages reported in previous categorization tasks (Sakamoto, 2010;Shport, 2008). In the same study using shared stimuli, L1 listeners' accuracy on a task that involved categorization (4AFC) of spoken accent patterns using visual representations of pitch contours was 61%, a difference suggesting that separate perceptual modes are invoked by these tasks (Strange & Shafer, 2008).…”
Section: Perception Task Typesupporting
confidence: 62%
See 3 more Smart Citations
“…At the opposite end of the perceptual spectrum are correctness judgment tasks, which require listeners to access a word's representation from memory, and can thus be used to examine lexical knowledge more directly than discrimination or categorization tasks. Goss and Tamaoka (2015) reported that L1 Japanese speakers from Tokyo-type accent regions were able to judge the correctness of highfrequency words at a mean accuracy of 93%, well above averages reported in previous categorization tasks (Sakamoto, 2010;Shport, 2008). In the same study using shared stimuli, L1 listeners' accuracy on a task that involved categorization (4AFC) of spoken accent patterns using visual representations of pitch contours was 61%, a difference suggesting that separate perceptual modes are invoked by these tasks (Strange & Shafer, 2008).…”
Section: Perception Task Typesupporting
confidence: 62%
“…Task type may influence the resources that listeners employ in speech perception. For instance, some tasks, such as same-different discrimination, primarily involve an acoustic mode of perception (Bent, Bradlow, & Wright, 2006), while others, such as lexical decision tasks and correctness judgments, are lexical as they require the comparison of a perceived stimulus to a representation in long-term memory (Goss & Tamaoka, 2015). Discrimination and categorization tasks are common in L2 perception studies and have been used to answer questions about how speech categories are established cross-linguistically (e.g., Shport, 2016;Wong & Perrachione, 2007).…”
Section: Perception Task Typementioning
confidence: 99%
See 2 more Smart Citations
“…For the 3-AFC task, participants were first given oral and printed instructions explaining the difference in pitch accent. Images taken from [24], which visually represented the three possible pitch patterns, were displayed on a computer monitor at all times. In each trial, participants heard a multisyllabic nonword over headphones and were asked to categorize the sound into one of three accent categories (corresponding to the onscreen pattern) as quickly and as accurately as possible through button press.…”
Section: Methodsmentioning
confidence: 99%